2020
DOI: 10.3389/fcell.2020.560266
|View full text |Cite
|
Sign up to set email alerts
|

Functional Peroxisomes Are Essential for Efficient Cholesterol Sensing and Synthesis

Abstract: Cholesterol biosynthesis is a multi-step process involving several subcellular compartments, including peroxisomes. Cells adjust their sterol content by both transcriptional and post-transcriptional feedback regulation, for which sterol regulatory element-binding proteins (SREBPs) are essential; such homeostasis is dysregulated in peroxisome-deficient Pex2 knockout mice. Here, we compared the regulation of cholesterol biosynthesis in Chinese hamster ovary (CHO-K1) cells and in three isogenic peroxisome-deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 87 publications
(178 reference statements)
2
17
0
Order By: Relevance
“…We did, however, obtain evidence that peroxisomal DCA β-oxidation provides acetyl-CoA units for other biochemical pathways such as ketogenesis. (Charles et al 2020;Fidaleo et al 2011;Kovacs et al 2004Kovacs et al , 2009Martens et al 2008;Nicolas-Francès et al 2014), in line with our findings in the liver of Ehhadh KO mice. Our observations are consistent with previous reports of reduced cholesterol synthesis rates in skin fibroblasts from patients with peroxisomal disorders (Hodge et al 1991).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We did, however, obtain evidence that peroxisomal DCA β-oxidation provides acetyl-CoA units for other biochemical pathways such as ketogenesis. (Charles et al 2020;Fidaleo et al 2011;Kovacs et al 2004Kovacs et al , 2009Martens et al 2008;Nicolas-Francès et al 2014), in line with our findings in the liver of Ehhadh KO mice. Our observations are consistent with previous reports of reduced cholesterol synthesis rates in skin fibroblasts from patients with peroxisomal disorders (Hodge et al 1991).…”
Section: Discussionsupporting
confidence: 92%
“…The role of peroxisomes in cholesterol metabolism remains a debated issue. In vitro and in vivo studies done in different models of peroxisomal deficiency have reported disturbances of cholesterol homeostasis and activation of the SREBP2 pathway (Charles et al 2020; Fidaleo et al 2011; Kovacs et al 2004, 2009; Martens et al 2008; Nicolas-Francès et al 2014), in line with our findings in the liver of Ehhadh KO mice. Our observations are consistent with previous reports of reduced cholesterol synthesis rates in skin fibroblasts from patients with peroxisomal disorders (Hodge et al 1991).…”
Section: Discussionsupporting
confidence: 91%
“…The peroxisome is amazingly versatile in its metabolic function, as reflected by the existence of many taxa‐specific proteins and pathways (Charles et al., 2020; Pan et al., 2020; Parsons, 2004). This versatility makes prediction of peroxisomal proteins highly valuable because it may lead to the discovery of new metabolic pathways in different species (Pan et al., 2020; Reumann & Chowdhary, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The role of peroxisomes in cholesterol biosynthesis has been a matter of controversy for years [12][13][14]. In fact, convincing evidence supporting a direct involvement of peroxisomes in cholesterol biosynthesis is still lacking, even in a latest study in favor of the viewpoint [15]. It is more likely that peroxisomes contribute to cholesterol homeostasis by transporting the molecule between different organelles and the plasma membrane (PM), which will be discussed in the later sections of this review.…”
Section: Peroxisomes In the Brainmentioning
confidence: 99%